Respostas
respondido por:
11
x² - 14x +33 = 0
a=1 b=-14 c=33
Δ=b²-4ac
Δ=(-14)²-4×1×33
Δ=196-132
Δ=64
x=-b⁺₋√Δ
a=1 b=-14 c=33
Δ=b²-4ac
Δ=(-14)²-4×1×33
Δ=196-132
Δ=64
x=-b⁺₋√Δ
respondido por:
15
Explicação:
x² - 14x +33 = 0
(14 +/- raiz quadrada (-142 -4 . 1, 33))/2. 1
(14 +/- raiz quadrada (196 -132))/2
(14 +/- raiz quadrada (64))/2
(14 +/- 8)/2
Primeira raiz: 22/2 = 11
Segunda raiz: 6/2 = 3
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás